Effects of a Longitudinal Crack in Overhung Rotor - Malta, Jhon; Bur, Mulyadi; Fadillah, Muhammad Rahmanda (LPPM Universitas Andalas, 2022)
In this study, a longitudinal crack simulation will be carried out on the shaft using the MSC Nastran/Patran to identify the effect of variations in the depth and length of the crack on the shaft on the stress distribution along the shaft and to determine the dynamic behavior of the rotor shaft overhung system due to cracks. The simulation was carried out with two models, with and without a crack. The first crack position locates between the disk and the bearing, and the second is between the two supports. Based on the simulation test results, the natural frequencies tend to decrease with increasing variations in the depth and length of the crack, especially at first and second natural frequencies. The cracks between the disc and the bearing significantly reduce stiffness than the cracks between the two supports. Furthermore, in the stress analysis, the cracks increase the rotor's maximum stress, which occurs in the area of the ultimate bending moment.